¿QUÉ ES LA DIALÉCTICA? - Alfaro Vargas, Roy (Universidad de Costa Rica, 2013)
This text is a lecture, whose original name is Was ist Dialektik?, given by Alexandre Kojève (1902-1968) at the Freien Universität Berlin, in June 26th, 1967, and reproduced by the Deutsche Zeitschrift für Philosophie, Berlín 50 (2002) 2, pp. 317-329. Kojève deals with dialectics through language. With this, he points out that language has a dialectical structure, since two opposite judgements in the same situation (the apple of Kojève) cannot be true at the same time, contrary to some (post)structuralist approaches that believe thatboth of them could be true. This translation fills some voids in relation to dialectics, in the context of a new rise of Marxism. All the footnotes in this translation belong to the translator.